Poverty and Price Transmission - Christian Elleby (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2014)
A key parameter determining the welfare impact from a world market shock is the transmission elasticity which measures the average domestic response to an international price change. Many studies have estimated price transmission elasticities for a large number of countries but the variation in these estimates is so far largely unexplored. This paper proposes a model which explains a country's domestic price response to world market shocks in terms of its demand structure. The model delivers two testable predictions; price transmission is increasing in per capita food expenditure and in income inequality. The empirical analysis of price changes during the food crises confirms these predictions with a caveat. I find significant inverse U-shaped relationships between domestic food price growth in 2007-8 and 2010-11 and per capita food expenditure. Unequal countries also experienced higher price growth but the relationship is less significant. The finding that food prices in middle-income countries increased the most during the food crises is a cause for concern in light of the fact that the majority of the world's poor today live in middle-income countries.
Keywords: D11; D31; Q11; Q12; 330; Price transmission; Food crisis; Food prices; Non-homothetic preferences; Income distribution